Comparative Evaluation of Production Performance in Improved Chicken Varieties for Backyard Farming - Niranjan, M.; Sharma, R.P.; Rajkumar, U.; Reddy, B.L.N.; Chatterjee, R.N.; Battacharya, T.K. (International Journal of Poultry Science, 2008)
The growth and production performance of 4 chicken varieties developed for backyard farming were evaluated in the present study. The body weights were significantly (p<0.05) varied in 4 chicken varieties. The body weights were significantly higher in C1 and Vanaraja and lower in Gramapriya. The C2 and C1 crosses matured early at the age of 145.72±1.11 and 154.67±0.81 days, respectively. The egg weights were significantly (p<0.05) higher in C1 cross throughout the laying period. The egg weights ranged from 57.06±0.27 g (Vanaraja) to 58.58±0.29 g (C1 cross) and 60.07±0.28 g (Vanaraja) to 61.34±0.35 g (C1 cross) at 40 and 64 weeks of age, respectively. The egg production in C1 cross was significantly (p<0.05) better than Vanaraja and C2 cross at all ages, however the egg production was on par with Gramapriya at 64 and 72 weeks of age. C1 cross has substantial production capabilities as dual purpose bird suitable for rural and backyard farming in the country.